Calophyllum-Inophyllum from Pahang Malaysia as Biolubricant Feedstock for Industrial Application - Amiril Sahab, Abdul Sani; Nor Athira, Jamaluddin; Ahmad Shahir, Jamaludin; Norfazillah, Talib (Springer, 2021)
Lubricant derived from Tamanu (Calophyllum-Inophyllum) fruits is a non-edible vegetable-based oil that is renewable, biodegradable and sustainable which could be added into the biolubricants products as feedstock for industrial application. The physicochemical properties of the crude Tamanu oil (CTO) including rheological, temperature and corrosion characteristicswere determined for suitability as base stock for lubricant production through comparison between the RBD palm olein (RBD-PO) and crude Jatropha oil (CJO). The lubricants underwent a series of analyses on their properties in terms of physical and chemical characteristics. The density, viscosity, flashpoint, water content, corrosion test, and acid value are measured following the ASTM standards. A four-ball wear test that was subjected to the CTO was conducted to determine its lubrication behavior for friction and wear resistance. Results have shown that the CJO has a better viscosity index compared to the CTO, whereas the CTO is better than the CJO in other measured properties. The properties of the Tamanu oil need to be improved except for its flash point and corrosion inhibition properties.